Welcome or Not: Comparing #Refugee Posts on Instagram and Pinterest. (April 2018) - Guidry, Jeanine P. D.; Austin, Lucinda L.; Carlyle, Kellie E.; Freberg, Karen; Cacciatore, Michael; Jin, Yan; Messner, Marcus
The Syrian refugee crisis, started in 2011, has resulted in millions of Syrians fleeing their homes: 6.6 million have been internally displaced and more than 4.6 million have fled the country. This flow of refugees has led to both humanitarian efforts to assist refugees and growing views of refugees as a threat to receiving countries' security and autonomy. Sentiments about the still-growing crisis are increasingly expressed on social media platforms, including visual ones like Instagram and Pinterest. However, little is known about what and how information about refugees is presented on these platforms. The current study addresses this gap by conducting a quantitative content analysis of a random sample of 750 Instagram posts and 750 Pinterest posts to evaluate and compare visual and textual messaging surrounding this crisis. Results show that Pinterest messages more frequently depict security-concern sentiment and include more unique visual components than Instagram. Across platforms, security-concern posts were more likely to be framed thematically; whereas most humanitarian-concern posts were framed episodically. The study concludes with a discussion of implications for communication scholars and practitioners that may inform the development of visual-based social-mediated messaging.